(untitled) (BIRDEM Medical Journal, 2014)
Objective: To evaluate parathyroid hormone (PTH) status among end stage renal disease (ESRD) patients on maintenance haemodialysis (MHD). Methodology: This descriptive cross-sectional study was done in the Department of Nephrology, BIRDEM General Hospital, Dhaka, from April to September 2011. Results: A total of 50 patients were included in this study with a 3:2 male predominance. Mean age was 54.6 (range 34-76) years. Mean duration of ESRD was 3.73 years. All the patients were diabetic and other common co-morbidities were hypertension (76%), dyslipidaemia (56%), ischaemic heart disease (48%) and stroke (12%). They were receiving calcium (72%), vitamin D (40%), both calcium and vitamin D (38%) supplementation and 20% were not on any medication for treatment of chronic kidney disease mineral bone disorder (CKD-MBD). Mean pre-dialysis values of urea and creatinine were 30.28 mg/dl and 8.67 mg/dl respectively. Mean (± SD) serum level of calcium, phosphate and PTH were 8.32 (±1.26) mg/dl, 4.42 (±1.54) mg/dl and 125.45±117.71 pg/ml respectively. In 76% of the study subjects, PTH level was above normal. Significant difference (P=<0.05) in PTH levels was observed among patients with and without any medication for prevention of CKD-MBD but the levels were within the acceptable range. Serum calcium level in the study subjects had significant positive relationship with serum PTH level. It was also observed that PTH level had significant negative relationship with phosphate level. Conclusion: PTH level was higher in ESRD patients on MHD specially those who were not on any medication than those who took calcium, vitamin D or both but it was still within the acceptable reference range. In such patients, serum calcium, phosphate and PTH levels should be monitored periodically. DOI: http://dx.doi.org/10.3329/birdem.v4i1.18547 Birdem Med J 2014; 4(1): 13-17